Variability and Diversity Studies Using Morpho-physiological Traits in Wheat (Triticum aestivum L.) under Irrigated and Rainfed Conditions - Rana, V.; Singh, M.; Rana, A. (International Journal of Bio-resource and Stress Management, 2024)
A study was conducted at Rice and Wheat Research Centre, Malan and Department of Genetics and Plant Breeding, CSK HPKV, Palampur, Himachal Pradesh, India during October, 2013 to May, 2014 to identify traits for developing reliable selection criteria and conduct diversity analysis. In the present investigation, fifty-six diverse wheat genotypes were evaluated in an alpha-design using various yield attributes and drought indices under irrigated and moisture-stress environments over three environments in two locations. Results from the study indicated significant differences for almost all the traits under all three environments and pooled environments. Variability studies showed high phenotypic and genotypic coefficient of variability with high heritability coupled with high genetic advance for seedling vigour under irrigated conditions as well as under moisture-stress conditions along with membrane stability index, dry matter accumulation and grain yield. On the basis of low DSI and high DRI values and relative ranking of morpho-physiological traits, seven genotypes HPW 368, NI 5439, CM 33, CM 19, HPW 236, CM 11 and HPW 349 have been found to be moisture-stress tolerant. Association studies showed that grains spike-1, harvest index, thousand grain weight, excised leaf water loss and days to 75% maturity are most important traits for selection of tolerant genotypes. On the basis of D2 statistics, 56 genotypes were grouped into twelve main clusters and genotypes HPW 277, HPW 297 and NIAW 1415 were found superior as well as diverse for most of the traits. Hence, these genotypes can be used in breeding programmes aimed at enhancing drought tolerance.